Executive‐level support for flexible work arrangements in a large insurance organization. (12th September 2016) - Williams, Penelope; McDonald, Paula; Cathcart, Abby
Abstract : Strategic workforce initiatives, such as flexible work arrangements (FWAs) are established at the executive level, yet executive support for FWAs has been given scant attention. This study applies Bowen and Ostroff's human resource (HR) process dimensions of distinctiveness, consistency, and consensus to explore how executives in a large Australian insurance company signal support for the implementation of flexible work policy to subordinate supervisors. The findings show that executives signal their support through explicit statements encouraging use of FWAs, through reporting, and by their own use of FWAs. Importantly, the findings also show that the strategic context influence how executives interpret and implement HR policy, in this case with an emphasis on profitability and risk aversion. This study contributes to knowledge about HR policy implementation and the role of executives in shaping a work environment supportive of FWAs. Key points: A critical dimension of support for flexible work arrangements (FWAs) is for executives to send signals encouraging take‐up. Executives need to model the use of FWAs and monitor and explicitly encourage subordinate use. Where policy is ambiguous, executives develop informal practices consistent with priorities in the business context. To address policy–practice gaps in FWAs, human resource managers should work with executives to communicate policy intent.